Pediatric Fulminant Hepatic Failure: Systematic Review: Life Sciences-Medicine - Abdelsamie Fadl, Ahmed; Musaad Masoud A, Almuthaybiri; Lama Kamal S, Kabrah; Amjad Abdullah H, Assiri; Khalid Mohammed M, Alahmadi; Bala Babkir Abd Alla, Yousra; Mohammed Darwish, Yassir; Ali Alaamree, Mohammed; Faroug Ahmed Abdelaal, Ahmed; Sulaiman Aljabarah, Norah; Abdulrahman Alwayli, Amaal; Helal Alazmi, Badriah (International Journal of Life Science and Pharma Research, 2022)
Abstract: Fulminant hepatic failure FHF in children is a rare but often fatal condition. Our understanding of this disorder is limited due to the disorder’s rarity. The majority of FHF cases in children have no known cause. The mechanisms by which hepatocytes undergo cell death are unknown. The aetiology and degree of CNS involvement influence the outcome. The study aims to summarize current evidence on the prevalence, risk factors and management approaches of irritable bowel syndrome in Saudi Arabia. For article selection, the PubMed database and EBSCO Information Services were used. All relevant articles relevant to our topic and other articles were used in our review. Other articles that were not related to this field were excluded. The data was extracted in a specific format that the group members reviewed. Seven studies were included and affirmed that mortality of fulminant hepatic failure is high, and the commonest aetiology is viral infections, particularly HAV. The peak level of total serum bilirubin, the rate of change of the prothrombin time/daily and ammonia level were significant predictors of mortality.